The Impact of Wafters on the Thermal Properties and Performance of In-Wheel Motor - Albana, Muhammad Hasan; Putra, Ary Bachtiar Khrisna; Guntur, Harus Laksana (World electric vehicle journal, 2024)
Electric vehicle (EV) proliferation is accelerating, characterized by the rising quantity of electric automobiles on global roadways. The electric machine is a crucial component of an EV, and the heat generated within the motor requires consideration as it impacts performance and longevity. A prevalent form of machine in EV is the in-wheel motor (IWM), which is notable for its compact size. However, it presents more significant cooling challenges. This research offers a new cooling method to cool the IWM. The system consists of wafters mounted on the housing of the IWM. Testing was conducted to determine the effect of wafters on the thermal properties and performance of IWMs. The machine used in this research is a brushless direct current (BLDC) motor featuring an outer rotor configuration and a peak power output of 1.5 kW. Testing was carried out experimentally and by simulation, and the simulation used Ansys Motor-CAD software. The research results show that applying wafers to IWM reduces the temperature of IWM components by up to 13.1%. IWM with wafters results in a torque increase of 0.14%, a power increase of 0.64%, and an efficiency improvement of 0.6% compared to IWM without wafters.